National survey of hepatitis B virus (HBV) polymorphism in asymptomatic HBV blood donors from 1999 to 2007 in France - Servant-Delmas, Annabelle; Mercier, Mélanie; El Ghouzzi, Marie-Hélène; Girault, Annie; Bouchardeau, Françoise; Pillonel, Josiane; Laperche, Syria (Transfusion (Philadelphia, Pa.), 2010)
BACKGROUND: Hepatitis B virus (HBV) diversity is characterized by eight genotypes correlated to eight hepatitis B surface antigen (HBsAg) subtypes, which differ in their geographical distribution. STUDY DESIGN AND METHODS: To establish virologic characteristics and the evolution of HBV diversity, we carried out a study over a 9‐year period in HBV‐infected French blood donors. HBsAg subtyping based on specific antibody method concerned 2901 donors, from whom 940 have been analyzed by an S‐gene sequencing to determine genotypes and S‐gene mutations. RESULTS: HBsAg subtypes were distributed as follows: ayw2, 34.4%; adw2, 25.7%; ayw1, 10.2%; ayw4, 14.9%; adr, 7.8%; ayw3, 6.4%; and adw4, 0.7%. Ayw4 (Genotype E) proportion increased over time in correlation with an increased proportion of subjects originated from sub‐Saharan Africa. The genotype observed with the highest proportion was D (43.0%), then A (26.2%), E (17.5%), B (6.5%), C (6.4%), and F (0.4%). Genotype B had the highest proportion of hepatitis B e antigen (39.2%) and the highest viral loads (VLs). Forty‐three (5.5%) isolates presented one (n = 35) or multiple (n = 8) amino acid envelope substitutions. Donors infected with mutated isolates had lowest VLs. rtA181T/sW172 stop mutation associated with resistance to nucleos(t)ide analogs was detected in two donors suggesting a transmission of these isolates. CONCLUSION: This extensive study shows that HBV genotype evolution is closely linked to the geographical origin of subjects and that the occurrence of viral envelope mutants is not an exceptional event in healthy HBV chronic carriers. Blood donors rarely recruited in HBV studies provide further relevant information on the characteristics of HBV diversity.